Comparative Study of The ATP Level of Swamp Buffalo (Bubalus bubalis) and Cow (Bos indices) Red Cells - Boonyun Sarikabhuti; Vorasak Patchimasiri; Suporn Pattamatum; Cheeraratana Cheeramakara; Suvit Areekul (Agriculture and Natural Resources, 1993)
The objective of this study was to compare the ATP level of normal swamp buffalo and cow red blood cells. Blood from thirty two swamp buffaloes and thirty indigeneous cows from Bangkhen, Bangkok were used for the determination of ATP by the luciferase enzyme. The avearge ATP level of normal buffalo red blood cells was 22.870±5.409 µmole/100 ml. while that of normal cow was 35.225±7.706 µmole/100 ml.